2013
DOI: 10.1111/acer.12116
|View full text |Cite
|
Sign up to set email alerts
|

Prazosin Reduces Alcohol Drinking Throughout Prolonged Treatment and Blocks the Initiation of Drinking in Rats Selectively Bred for High Alcohol Intake

Abstract: BACKGROUND This study examined whether prazosin reduces alcohol drinking over the course of prolonged treatment and whether it blocks initiation of alcohol drinking in rats with a genetic predisposition toward high alcohol drinking, i.e, alcohol-preferring (P) rats. METHODS In study one, alcohol-experienced P rats that had been drinking alcohol 2 hrs/day for several months were treated daily with prazosin (0, 0.5, 1.0 or 2.0 mg/kg BW) for 7 weeks. In study two, alcohol-naïve P rats were treated daily with pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
59
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(69 citation statements)
references
References 43 publications
10
59
0
Order By: Relevance
“…These results are consistent with our reports that prazosin, which decreases noradrenergic signaling by blocking post-synaptic α 1 -adrenergic receptors, decreases alcohol drinking in P rats when administered acutely (Rasmussen et al, 2009) or chronically (Froehlich, Hausauer, Federoff, et al, 2013;). The fact that two different pharmacologic interventions that decrease noradrenergic signaling, but via different mechanisms, are both capable of suppressing alcohol drinking is consistent with evidence that activation of the noradrenergic system plays a key role in mediating voluntary alcohol drinking.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are consistent with our reports that prazosin, which decreases noradrenergic signaling by blocking post-synaptic α 1 -adrenergic receptors, decreases alcohol drinking in P rats when administered acutely (Rasmussen et al, 2009) or chronically (Froehlich, Hausauer, Federoff, et al, 2013;). The fact that two different pharmacologic interventions that decrease noradrenergic signaling, but via different mechanisms, are both capable of suppressing alcohol drinking is consistent with evidence that activation of the noradrenergic system plays a key role in mediating voluntary alcohol drinking.…”
Section: Discussionsupporting
confidence: 93%
“…Prazosin dose-dependently reduced withdrawal-induced operant self-administration of alcohol in alcohol-dependent Wistar rats (Walker, Rasmussen, Raskind, & Koob, 2008). Prazosin also suppressed voluntary alcohol drinking by rats selectively bred for alcohol preference (P line) when administered either acutely (Rasmussen, Alexander, Raskind, & Froehlich, 2009) or chronically (Froehlich, Hausauer, Federoff, Fischer, & Rasmussen, 2013; Froehlich, Hausauer, & Rasmussen, 2013). The ability of prazosin to reduce alcohol drinking has been confirmed in humans; Simpson and colleagues (2009) reported that prazosin decreased relapse alcohol drinking in treatment-seeking alcohol-dependent men.…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated that prazosin treatment acutely and chronically decreases voluntary alcohol drinking in P rats (Rasmussen et al, 2009;Froehlich et al, 2013), alcohol drinking in a rat model of relapse to alcohol drinking (Froehlich et al, 2015), alcohol seeking and drinking in operant paradigms (Verplaetse et al, 2011), and drinking during acute withdrawal in alcoholdependent outbred rats (Walker et al, 2008). Prazosin treatment also facilitates abstinence in treatment-seeking alcohol-dependent men, as demonstrated in a study in which the subjects were unaware of their treatment condition (prazosin vs placebo) and there were no differences in side effects reported (Simpson et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggests that the noradrenergic system plays a key role in mediating ethanol-motivated behaviors in both alcohol-dependent and non-dependent humans and rats (Froehlich et al 2013a,b; Fox et al 2012; Gilpin and Koob 2010; Rasmussen et al 2009; Simpson et al 2009; Verplaetse et al 2011; Walker et al 2008). Prazosin, an α 1 -adrenergic antagonist, has been found to reduce ethanol drinking in home cage, limited access paradigms in P rats (Rasmussen et al 2009) and block operant responding for ethanol in dependent Wistar rats, with higher doses necessary to be effective in non-dependent animals in a fixed ratio (FR) paradigm (Walker et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Prazosin, an α 1 -adrenergic antagonist, has been found to reduce ethanol drinking in home cage, limited access paradigms in P rats (Rasmussen et al 2009) and block operant responding for ethanol in dependent Wistar rats, with higher doses necessary to be effective in non-dependent animals in a fixed ratio (FR) paradigm (Walker et al 2008). Prazosin blocks stress-induced reinstatement of ethanol-seeking in Wistar rats (Le et al 2011), and reduces ethanol drinking throughout prolonged treatment in alcohol-experienced P rats and impedes acquisition of ethanol drinking in naïve P rats (Froehlich et al 2013b). In the same paradigm used in the present investigation, prazosin attenuated ethanol- and sucrose-seeking and consumption in P rats (Verplaetse et al 2012).…”
Section: Introductionmentioning
confidence: 99%